Enhanced Predictive Capability of a 1-Hour Oral Glucose Tolerance Test: A Prospective Population-Based Cohort Study - Pareek, Manan; Bhatt, Deepak L.; Nielsen, Mette L.; Jagannathan, Ram; Eriksson, Karl-Fredrik; Nilsson, Peter M.; Bergman, Michael; Olsen, Michael H. (Diabetes care, 2018)
To examine whether the 1-h blood glucose measurement would be a more suitable screening tool for assessing the risk of diabetes and its complications than the 2-h measurement. We conducted a prospective population-based cohort study of 4,867 men, randomly selected from prespecified birth cohorts between 1921 and 1949, who underwent an oral glucose tolerance test with blood glucose measurements at 0, 1, and 2 h. Subjects were followed for up to 39 years, with registry-based recording of events. Discriminative abilities of elevated 1-h (≥8.6 mmol/L) versus 2-h (≥7.8 mmol/L) glucose for predicting incident type 2 diabetes, vascular complications, and mortality were compared using Kaplan-Meier analysis, Cox proportional hazards regression, and net reclassification improvement. Median age was 48 years (interquartile range [IQR] 48-49). During follow-up (median 33 years [IQR 24-37]), 636 (13%) developed type 2 diabetes. Elevated 1-h glucose was associated with incident diabetes (hazard ratio 3.40 [95% CI 2.90-3.98], < 0.001) and provided better risk assessment than impaired glucose tolerance (Harrell concordance index 0.637 vs. 0.511, < 0.001). Addition of a 1-h measurement in subjects stratified by fasting glucose provided greater net reclassification improvement than the addition of a 2-h measurement (0.214 vs. 0.016, respectively). Finally, the 1-h glucose was significantly associated with vascular complications and mortality. The 1-h blood glucose level is a stronger predictor of future type 2 diabetes than the 2-h level and is associated with diabetes complications and mortality.